ENRICHING VOCABULARY MASTERY USING SHORT STORIES (A Classroom Action Research in the Second Year of SMP N 5 Sukoharjo in the Academic Year of 2009/2010) - Risqi Ekanti Ayuningtyas Palupi (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2015)
This study is based on the problems of the low vocabulary mastery of the second year students of SMP N 5 Sukoharjo in the academic year of 2009/2010. It focuses on knowing whether using short stories can enrich the students vocabulary. It also focuses on the improvement of the students achievement in teaching learning process using short stories.The materials implemented in this research were short stories. The procedure of the research consisted of identifying the problems, planning the action, implementing the action, observing or monitoring the action, reflecting the result of the observation, and research findings. The research was conducted in a cycle. The cycle consisted of four meetings. Techniques in collecting the data were qualitative and quantitative method. In the qualitative method, the researcher used observations, field notes, photographs, and document analysis. The results of the observation were in the form of field notes and photographs. In the quantitative method, the researcher used tests. The test consisted of the pre-test and post-test. The technique to analyze the test result was by comparing the mean score of pre-test and post-test. Besides that, this research also used descriptive statistics and the t-test of non-independent.The results of this research show that short stories can improve the students vocabulary mastery. The improvement can be seen in the form of students achievements. They can be seen from the aspects of vocabulary mastery and the students motivation. First, from the aspect of the vocabulary mastery, the students could understand, grasp, remember, pronounce, write about 75 until 80 % of the words correctly and also use the words in context appropriately. Then, the improvement of students score can be seen from the differences between the pre-test and post-test. The mean score of the pre-test improves from 4.07 to 7.36 in post-test. Then, the scores of the pre-test and post-test show that there is also an improvement of students who achieve the minimum standard score, that is 60. They are from 2.8% to 94.3% of students. The test result shows that there is a significant improvement of the students vocabulary after the researcher conducted the research. The difference between the pre-test and post-test scores is 3.30; while the coefficient of the t-test between the pre-test and post-test is 19.29. Meanwhile, the t-tablefor 35 students is 2.04. Sinceis higher than, it means that there is a significant difference between pre-test and post-test score. Second, from the students motivation, the students are more active and enthusiastic during teaching learning process. Next, they have more concentration to do the exercises. Then, they do not do something useless during teaching learning process. At last, they also like having discussion with their friends.